Substantiation of the project of development of charging stations network for electric cars - Pulina, Tetiana; Shmygol, Nadiia; Narivs'kyi, Oleksii; Khmara, Natali; Shmygol, Yevgeniia (<center>Conference Proceedings Determinants Of Regional Development</center>, 2021)
Today, the global world market is slowly but surely and systematically developing a crisis in the extraction, processing and use of light hydrocarbons, i.e. oil and gas. It has two aspects, in particular the cost  of extracting these energy sources is constantly increasing, as deep drilling of wells on land, seas and oceans  is required, and the increasing combustion of these hydrocarbons pollutes the environment, contributing to global climate change. In addition, the latter has a very negative impact on human health, which requires considerable funds for their treatment, in particular, and leads to global extinction of both animals and humans in general. An alternative to light hydrocarbons for refueling and moving cars at the moment is electricity. After all, in addition to nuclear energy, alternative "green" energy has been intensively developed recently, which is generated by the energy of the sun, wind, water, organic compounds and household waste.  According to the results of the analysis of the dynamics of electric vehicles supply to Ukraine and construction of electric charging stations for their power supply, it was established that this type of transport moves 2.25 times more intensively on the market than building of electric charging stations. This slows down the promotion of this mode of transport in the country and does not reduce the consumption of traditional fuels, including gasoline and diesel fuel. Therefore, the article is devoted to the development of the concept of building a national network of charging stations by 2025, with serial production of 200 units per year, which is based on the capabilities of the company "Elekar Group" LLC. It is substantiated the project of production of electric charging stations, which is based on the deep analysis of the market, applying M. Porter's model  of competitiveness, SWOT-analysis and analysis of a life cycle of production. A conceptual model for diagnosing the competitiveness of charging stations has been developed.